SUCCESSFUL REMOVAL OF THE B-CELL LYMPHOMA OF THE RIGHT HEART AND THE TRICUSPID VALVE REPLACEMENT IN A HIV-INFECTED PATIENT - M. A. Martakov; M. V. Vishnyakova; M. V. Vishnyakova (jr.); V. P. Pronina; B. V. Ivashkin; V. A. Dudakov; V. T. Selivanenko; A. G. Osiyev (Неотложная медицинская помощь)
ABSTRACT. Primary B-cell lymphoma of the heart is an extremely rare disease. We report a case of successful removal of the right heart B-cell lymphoma and the tricuspid valve replacement in a hIV-infected patient. The use of modern diagnostic procedures and aggressive surgical management allow clinical effect in this category of patients to be achieved.